Equal and inclusive opportunity to access and use of ICT-based crop extension services for farm-level actors in Rwanda: a case study of the ICT4BXW project - Blom, F. (Wageningen University & Research, 2020)
All farmers around the world have a need for information. Information communication technology (ICT) could make access to information easier (Palumbo, 2013) (Aker & Mbiti, 2010) (van Winden, 2011). Others do however claim that the use of ICT excludes certain users from accessing information (Diga, Fortune, & Plantinga, 2013) (Njoki & Wabwoba, 2014) (Waugaman, 2016). Not only the use of ICT but also the design of the ICT platform could exclude users from access to information (Clarkson, Dong, & Keates, 2003). It is therefore important to understand the interaction between an ICT application, its design process, its use and the excluding or including aspects that affect access to information. This research aims to answer: ‘how does the introduction of a crop extension app, developed according to Human centred Design (HCD) approach, influences access to and use of extension services for farm level actors?’. This research took the case of ICT4BXW which uses a crop extension app at village level to control and prevention Banana Xanthomonas disease (BXW) in Rwanda. This research is tackled through process tracing of the user representation in a design process and technography to understand the implications and process of introducing a crop extension app at village level. Process tracing showed that the user representation, project assumptions and expectations changed over time. The results of process tracing show that the user’s role for the ICT4BXW app changed from providing information to receiving information. The expectations of the project on smartphone capacity was adapted and creating impact in disease occurrence changed to focus on learning from the design process. These changes of user representation were coevolving based on what user representatives gave as input, changing perspectives of project partners and as a response to unforeseen challenges. Process tracing showed that almost all feedback provided in the period of participatory workshops, including feedback of user representatives was adopted and included in the design. The feedback that was provided after these workshops was not always adopted or took time to be implemented. Introducing the ICT4BXW app meant for the farmer promoters that they had to visit all individual banana farmers in their village to register farmers, diagnose BXW and provide BXW information to farmers. Before introducing the ICT4BXW app, the farmer promoters would share this information in a collective village meeting. The farmer promoters experience that by introducing this app more time investment is required from them to provide extension services. The farmer promoters are additionally requested to visit the sector agronomist once a week to upload data. 8 out of 17 farmer promoters mention that the time investment and distance to visit the sector agronomist is a challenge. The project partners assume and expect that both farmer promoters and sector agronomists are willing and able to spend this extra time. By introducing this app, the farmer promoters also need to learn how to work with a smartphone, observations and interviews show this is sometimes challenging. On a positive note, after introduction of this app farmer promoters do experience more trust from farmers in the information they provide. The results of this research show that there are different levels of involvement and power among project partners and user representatives in making design decisions. In the first stage of the project users were not represented yet and design decisions were based on the imagination of project partners. Some of these design decisions resulted in forms of exclusion. In the second stage, user representatives were included to influence design decisions through participatory design workshops. Final design decisions were however always made by project partners. Most design decisions on which user representatives had an influence created inclusion for the application. Farmers were not directly represented during the design process but represented through the imagination and experiences of farmer promoters. This representation or lack of representation is reflected in the design of the app in which the farmer promoter plays a central role in order to access information on BXW for farmers. This does not create full exclusion for farmers to access information, but it creates dependency on the farmer promoter. Given the limited time/capacity of farmer promoters to visit farmers at home this is likely to result is less farmers having access to BXW information. The results in the ICT4BXW case indicate that the HCD approach still includes politics in design since project partners chose when, how and how often users would be represented in the design phase. This thesis showed that the form of user representation is affecting if design decisions of a crop extension app result in more inclusive or exclusive access to BXW information. HCD should therefore not be seen as utopia, panacea or solution to solve political/power concerns, exclusion and assumptions in design. By analysing the practices of the farmer promoter, this thesis has shown that the introduction of this crop extension app affected roles, responsibilities and dynamics of farmer promoters, sector agronomists and farmers in the existing extension system. This research shows that use of ICT does not automatically guarantee greater access to information. Precautions must be taken in the design process of ICT to ensure equal and inclusive access to information.